2017
DOI: 10.1177/1369433217693629
|View full text |Cite
|
Sign up to set email alerts
|

Model updating of suspended-dome using artificial neural networks

Abstract: Differences between the practical suspended-dome and the corresponding numerical model are inevitable. To reduce the existing discrepancy, model updating of a suspended-dome was investigated using the back-propagation network in the article. The article first proposed a method to increase the prediction precision of back-propagation network: reducing the range of the training data for the back-propagation network according to the previous prediction results continuously. Then, some parameters that can be measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Collapse of buildings during earthquakes causes serious casualties and economic losses. Much research has been carried out on recent years carried out by Chinese and foreign experts on the mechanical properties and stability of the string dome structure, such as seismic response and anti-seismic analysis [5][6][7][8], buckling and dynamic response under friction [9], model optimization design based on artificial neural networks [10], elastoplastic dynamic response [11], structural optimization algorithm and design [12][13][14], long-span discontinuous mechanical properties [15], initial geometric defect analysis [16], cable tension estimation [17], static and the dynamic analysis by finite element method [18,19], and thrust line analysis of masonry domes [20]. Gong, S.Y.…”
Section: Introductionmentioning
confidence: 99%
“…Collapse of buildings during earthquakes causes serious casualties and economic losses. Much research has been carried out on recent years carried out by Chinese and foreign experts on the mechanical properties and stability of the string dome structure, such as seismic response and anti-seismic analysis [5][6][7][8], buckling and dynamic response under friction [9], model optimization design based on artificial neural networks [10], elastoplastic dynamic response [11], structural optimization algorithm and design [12][13][14], long-span discontinuous mechanical properties [15], initial geometric defect analysis [16], cable tension estimation [17], static and the dynamic analysis by finite element method [18,19], and thrust line analysis of masonry domes [20]. Gong, S.Y.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of structural failure, typical failure modes of reinforced concrete columns such as flexure, flexure-shear, and shear were investigated by Mangalathu et al [50,51] using decision trees (DT), SVM, and ANN. Guo et al [52,53] employed the ANN model for the identification of damage in different structures such as suspended-dome and offshore jacket platforms. Regarding structural uncertainty analysis, various published works by E. Zio should be consulted [54][55][56].…”
Section: Introductionmentioning
confidence: 99%
“…Mangalathu et al [8,9] considered various machine learning techniques to identify the failure modes of beam-column joints and to estimate the shear strength. Guo et al [10] applied artificial neural networks (ANNs) to examine the model updating of a suspended dome considering both experimental and numerical models. In another work, Guo et al [11] proposed using partial modal results in the damage identification of offshore jackets and found that the prediction errors are sensitive to damage locations.…”
Section: Introductionmentioning
confidence: 99%